The Rapid Learning Shift In The Time Of Covid-19: Exploring The Efl Learners’ Speaking Anxiety - K. Dedy Sandiarsa; Abdul Kadir Bagis; Dedi Sumarsono (The Center for Language Development, Mataram State Islamic University., 2021)
The rapid learning shift due to the existence of Covid-19 was mandatory to be conducted at school. Due to this matter, the teaching and learning approach has been shifted from having face-to-face interaction in the classroom to distance learning and to the mixture between face-to-face interaction and distance learning. The goal of the research was to figure out the EFL learners’ anxiety due to the rapid shift learning in this covid-19 pandemic. This study was conducted at second grade students of SMAN 8 Mataram. The finding shows that a high level of anxiety of the EFL learners’ contribute to the students speaking performance. When building communication with others, the EFL learners speaking skill were not performed well due to their high speaking anxiety. The main causes of the EFL learners anxiety were lack of confidence, fear of making mistakes, lack of practice, and low speaking skill level.